Modified isolation method of Arcobacter spp. from different environmental and food samples - Šilha, David; Šilhová-Hrušková, Lucie; Vytřasová, Jarmila (Folia microbiologica, 2015)
This study provides information on the occurrence of Arcobacter in several types of water and food products of animal origin in the Czech Republic. We processed 190 samples using the modified method, and the occurrence of Arcobacter spp. was confirmed in 36.8 % of these. This total incidence consisted of Arcobacter butzleri (27.3 %), Arcobacter cryaerophilus (8.4 %) and Arcobacter skirrowii (1.1 %). We newly described the common presence of Arcobacter spp. in sewage water in the Czech Republic that is released into waterways after processing in water treatment plants (86.7 %). All the acquired isolates were subject to detailed confirmation with subsequent species classification using multiplex PCR and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). In this study, we used a modification of a method using passive filtration of an enriched sample, which could be suitable for the isolation of Arcobacter, especially in combination with Campylobacter selective agar chromogenic medium. Our studies have shown this agar to be quite suited to the isolation of Arcobacter and that it can be an appropriate instrument for accelerating culture diagnostics.
Keywords: Česká republika; Czech Republic; odpadní vody; počet mikrobiálních kolonií; Culture Media; Arcobacter; Colony Count, Microbial; Sewage; Food Microbiology; kultivační média; potravinářská mikrobiologie